Novel comparison concept between CBN and Al2O3 grinding process for eco-friendly production - Sato, Bruno Kenta [UNESP]; Lopes, José Claudio [UNESP]; Rodriguez, Rafael Lemes [UNESP]; Garcia, Mateus Vinicius [UNESP]; Mia, Mozammel; Ribeiro, Fernando Sabino Fonteque [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Elsevier, 2022)
Minimal Quantity of Lubrication was developed to achieve green manufacturing in machining process. In this study, parameters of cutting fluid flow, grinding wheel type and wheel cleaning system were evaluated to achieve the maximum potential of this technique in grinding process. The comparison of super abrasive (CBN) and conventional (Al2O3) grinding wheel, the cutting fluid flow (30 ml/h, 60 ml/h and 120 ml/h), and the wheel cleaning system were analyzed based on: surface roughness, roundness errors, grinding wheel wear, confocal of grounded surface, grinding power, acoustic emission and workpiece microscopy. In a novel way, this study compared the costs per piece and the carbon footprint in terms of CO2 emission for both abrasive tool application. For all the parameters analyzed, the CBN grinding with MQL outperformed the Al2O3 grinding, showing a superior performance not only in terms of surface finishing, on average, 29% lower surface roughness and dimensional deviation 9% lower but also regarding tool efficiencies, such as 127% lower diametrical wear, 42% lower acoustic emission, and 13% lower grinding power. Despite that, the cost per piece was also evaluated for the different lubri-cooling conditions and tools, and the cost per piece recorded for Al2O3 grinding was substantially lower than CBN grinding, irrespective of the lubri-cooling method employed. The cost of grinding for all MQL techniques analyzed with aluminum oxide wheel was, on average, 72% less than grinding with CBN wheel. Besides, the conventional method with the CBN wheel was 7% more expensive than the aluminum oxide wheel.
Keywords: Grinding; Minimum quantity of lubricant; Wheel cleaning; Wheel clogging